2019
DOI: 10.1136/bmjopen-2019-031132
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of sickness absence after road traffic injury: a Swedish register-based cohort study

Abstract: ObjectivesDespite much focus on the health impact of road traffic injury (RTI) on life, there is a lack of knowledge of the dynamic process of return to work following RTI and its related factors. The aim of this study was to identify longitudinal patterns of sickness absence (SA) following RTI, to examine the patterns’ interplay with health-related quality of life (HRQoL) and to determine if there are differences, regarding the patterns and interplay, according to injury severity.DesignA register-based prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…The association between SA and hospitalisation was also observed in two previous old and relatively small studies [ 12 , 13 ]. Likewise, the association between age and SA and/or DP is consistent with previous studies reporting on this association [ 7 , 10 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The association between SA and hospitalisation was also observed in two previous old and relatively small studies [ 12 , 13 ]. Likewise, the association between age and SA and/or DP is consistent with previous studies reporting on this association [ 7 , 10 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study we found that 66% had no or little SA and DP during the three follow-up years. This is in line with a Swedish study using group-based trajectory models, where 76% of the included 903 individuals who had a road traffic injury were found in a pattern with a low number of SA days during the three-year follow-up [ 10 ]. However, that study did not consider DP during the follow-up nor were different road user groups specified.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In terms of net days SA/DP, a threshold of PMI ≥1% seems to capture a majority of the increase in SA and DP due to injury after a car crash, and could from that perspective be recommended as a target for policy and action to prevent such consequences. Regarding MAIS 3+, Rissanen et al has shown that road traffic injuries classified MAIS 3+ resulted in a higher number of SA days immediately after the crash which is then more quickly reduced, compared to less severe injuries 109 . This can be compared to the findings regarding WAD (an injury classified as AIS 1) in this thesis.…”
Section: Associations Between Permanent Medical Impairment and Sicknementioning
confidence: 99%
“…The risk of being injured in motor vehicle crashes has been found higher in general among those of older age in many studies 65,[124][125][126] . Older individuals have also been shown to have lower functioning and health after a crash 127 , and individuals with a slow decrease of gross SA days in the period after a crash are more often older than those with a quicker decrease 109 . Although, some specific injury types can have more severe consequences among younger age groups.…”
Section: Sociodemographic Factorsmentioning
confidence: 99%